EFEK KETERBUKAAN PERDAGANGAN PADA VOLATILITAS NILAI TUKAR - Wayrohi Meilvidiri; Syahruddin Syahruddin; Romualdus Turu Putra Maro Djanggo (Universitas Musamus,Merauke,Papua, 2019)
This study uses the q to q dataset for the period 2011-2018, to examine the effect of trade openness on the exchange rate, on the other hand variable money supply, inflation and GDP growth and high-low exchange rates (dummy) will smooth the impact of shocks to the exchange rate . Using the OLS econometric estimator to see the effect of variables and the ARCH method to measure the uncertainty of exchange rate movements. Estimation results show that trade openness (open trade index); the money supply (money supply) and the high-low peak value of the exchange rate have a significant positive effect while the growth variable has a significant negative effect on exchange rate volatility. The LM test simultaneously found ARCH in residual data in lag 1 and lag 2. The normality test found abnormal residuals, while the residual heteroscedasticity test showed no ARCH problems in the last residuals.